Inequity and injustice: recognizing infertility as a reproductive justice issue - Jamila Perritt, M.D., M.P.H; Natalia Eugene, B.S (Elsevier, 2022)
In recent years, as knowledge of the tenets of reproductive justice has increased, the framework has garnered increasing attention in media, public health, and public policy spaces. Nevertheless, one domain of the reproductive justice framework is frequently overlooked-the right to have a child; specifically, we refer to the right and ability access to infertility treatment and services. Black, Indigenous, and other people of color, those living on low incomes, and other historically marginalized communities often experience disparate access to infertility evaluation, treatment, and care. This commentary aims to explore the inequities that exist for those seeking fertility services and advocate for examining and addressing these inequities using a reproductive justice lens.